The usage of TikTok as a marketing tool among small business entrepreneurs in Malaysia - Mohamad, Mohd Amin; Hamzan, Puteri Nor Hanis (Research and Scientific Innovation Society, 2025)
This study investigates the usage of TikTok as a marketing tool among small business entrepreneurs in Malaysia, focusing on the factors that influence its adoption and its effect on perceived business performance. Grounded in the Technology Acceptance Model (TAM), the research examines the roles of Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Interactivity (INT) in predicting TikTok Usage (TU). A quantitative research design was employed using a structured questionnaire distributed to small business owners, and the data were analyzed using Structural Equation Modeling (SEM) via AMOS. The model demonstrated an acceptable fit, with RMSEA = 0.077, CFI = 0.933, and Chi-square/df = 1.589. Of the three hypotheses tested, only the relationship between PEOU and TU was statistically significant (p = 0.012), indicating that ease of use is a key driver for entrepreneurs adopting TikTok. In contrast, PU and INT did not significantly influence TU. These findings suggest that while small business owners find TikTok easy to use, it may not yet be viewed as a performance driven platform without strategic content planning and engagement. This study contributes to TAM literature by contextualizing it within a modern social media environment and offers practical insights for entrepreneurs, digital trainers, and policy-makers. It also highlights the needs for future research to include moderating variables, qualitative approaches, and platform comparisons to further understand TikTok’s role in SME digital marketing.